Answer:
(x - 43)(x + 3)
Step-by-step explanation:
consider the factors of the constant term (- 129) which sum to give the coefficient of the x- term (- 40)
the factors are - 43 and + 3 , since
- 43 × + 3 = - 129 and - 43 + 3 = - 40 , then
x² - 40x - 129 = (x - 43)(x + 3) ← in factored form
Answer:
i think maybe D
Step-by-step explanation:
Normally a equation has to have an equal sign and all the numbers add up
-4/2=-2
(-2)^2=4
the blank is +4
x^2-4x+4
factored
(x-2)^2
Answer:
fraction 1 and 3 over 5
Step-by-step explanation:
2:3 is equal to 8 blocks
5:12 is equal to 5 blocks
if you divide them, the result is:
8/5 which is the same as 1 3/5
because 5 is contained 1 time in 8 and the rest is 3